2008
DOI: 10.1038/ng.173
|View full text |Cite
|
Sign up to set email alerts
|

Ras-MAPK signaling promotes trophectoderm formation from embryonic stem cells and mouse embryos

Abstract: In blastocyst chimeras, embryonic stem (ES) cells contribute to embryonic tissues but not extraembryonic trophectoderm. Conditional activation of HRas1(Q61L) in ES cells in vitro induces the trophectoderm marker Cdx2 and enables derivation of trophoblast stem (TS) cell lines that, when injected into blastocysts, chimerize placental tissues. Erk2, the downstream effector of Ras-mitogen-activated protein kinase (MAPK) signaling, is asymmetrically expressed in the apical membranes of the 8-cell-stage embryo just … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
117
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(128 citation statements)
references
References 29 publications
(3 reference statements)
8
117
1
2
Order By: Relevance
“…In addition to the ExEn lineage, we also detected elevated expression of some trophectoderm marker genes after overexpression of Stk40, which is in agreement with a recent finding that inducible induction of Ras at low levels promoted expression of marker genes for both trophectoderm and primitive endoderm lineages (29). However, they also found that trophectoderm markers predominated at higher levels of Ras (29).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In addition to the ExEn lineage, we also detected elevated expression of some trophectoderm marker genes after overexpression of Stk40, which is in agreement with a recent finding that inducible induction of Ras at low levels promoted expression of marker genes for both trophectoderm and primitive endoderm lineages (29). However, they also found that trophectoderm markers predominated at higher levels of Ras (29).…”
Section: Discussionsupporting
confidence: 80%
“…However, they also found that trophectoderm markers predominated at higher levels of Ras (29). Thus, it seems that the effect of Ras activation is dependent on developmental and cellular contexts as well as its activation levels.…”
Section: Discussionmentioning
confidence: 98%
“…Subsequently, we generated a doxycycline-dependent knockdown stable ES cell line and the ES cells were injected into the nude mice as described [39] (Figure 6A). Teratoma development was monitored by determination of endoderm, mesoderm and ectoderm (Supplementary information, Figure S11C).…”
Section: The Effect Of Fbw7 On the Development Of Blood Vessels In A mentioning
confidence: 99%
“…Knowledge of signaling pathways and transcription factors that reinforce these three lineages in the blastocyst has pointed to ways to alter the developmental potential of the stem cell lines derived from the blastocyst's lineages. For example, ESCs can be converted to TSCs by overexpressing the TE-specific transcription factor CDX2 in TSC medium [16] and by other means [17][18][19][20][21]. Importantly, overexpression of Cdx2 in ESCs leads to TSC-like cells with highly similar morphology, developmental potential, and gene expression as embryoderived TSCs [16,22,23].…”
Section: Introductionmentioning
confidence: 99%